The Importance of Entrepreneurship as a Contributing Factor to Economic Growth and Development: The Case of Selected European Countries - Meyer, Natanya; de Jongh, Jacques (Journal of Economics and Behavioral Studies, 2018)
Entrepreneurship has been pointed out as a key contributor to sustained economic growth and development as it not only creates employment, but increased spending in markets, knowledge transfers, employment and innovation. However, very few studies exist that empirically measures the relationship between the three variables; economic growth, economic development and entrepreneurship. Therefore, the purpose of this study is to determine and highlight the importance of entrepreneurship as a contributing factor to economic growth and development. Traditionally, economic growth is measured by the gross domestic product (GDP) of a country. As no formal measurement of economic development exists, an index was created taking into consideration the Human Development Index (HDI), percentage population above the poverty line and employment rate. The entrepreneurship development variable is measured by the Total Early-Stage Entrepreneurial Activity (TEA). The study followed a quantitative research design and made use of secondary time series data with the sample period ranging from 2005 to 2016. The study area comprised five selected member states of the European Union (EU) which included Germany, the Netherlands, Hungary, Belgium and Poland. Findings suggest that economic growth, development and entrepreneurship seem to be inexplicably connected. As several other factors may also contribute to the fluctuations of economic growth and development results differed from one country to another. However, the analyses from the Dutch, Hungarian and Polish economies for the period under consideration reveal correspondingly healthy economic and social environments where entrepreneurial climates are flourishing. The analysis from Germany and Belgium, however reveal subdued entrepreneurial development. Based on these findings, it is recommended that the development of SME sectors especially in transition economies be centralised as important focus areas towards improving economic and social growth outlooks. In turn, policy stakeholders should ensure the creation of enabling environments structured around responsive micro and macro decision-making.